Non-EFL students' perspectives on English learning in higher education institution: The case of Indonesian non-English major - Putra, Rizky Anugrah; Suparni, Suparni (LingTera, 2023)
The annulment of English subject at the elementary and tertiary levels harms the absorption of graduates. This decision needs to be reviewed whether it follows current conditions where graduates are required to be able to compete globally. Competition becomes increasingly problematic because students lack continuous English learning. This study aims to reveal the perspectives of non-EFL students on learning English in their faculties and how the association between English learning achievement scores and their perspectives on the language they are learning is related. It involved 45 students from two non-English faculties who studied English only as a general course. Our statistical calculations using correlation analysis found that most non-EFL students had an optimistic viewpoint on English and hoped to be provided with it continuously. In addition, the analysis also found that the achievement scores in English lessons had a significant positive correlation with their perspectives.